Dysregulated TRAF3 and BCL2 Expression Promotes Multiple Classes of Mature Non-hodgkin B Cell Lymphoma in Mice - Perez-Chacon, Gema; Adrados, Magdalena; Vallejo-Cremades, Maria T.; Lefebvre, Sophie; Reed, John C.; Zapata, Juan M. (Frontiers in Immunology, 2019)
TNF-Receptor Associated Factor (TRAF)-3 is a master regulator of B cell homeostasis and function. TRAF3 has been shown to bind and regulate various proteins involved in the control of innate and adaptive immune responses. Previous studies showed that TRAF3 overexpression renders B cells hyper-reactive to antigens and Toll-like receptor (TLR) agonists, while TRAF3 deficiency has been implicated in the development of a variety of B cell neoplasms. In this report, we show that transgenic mice overexpressing TRAF3 and BCL2 in B cells develop with high incidence severe lymphadenopathy, splenomegaly and lymphoid infiltrations into tissues and organs, which is the result of the growth of monoclonal and oligoclonal B cell neoplasms, as demonstrated by analysis of VHDJH gene rearrangement. FACS and immunohistochemical analyses show that different types of mature B cell neoplasms arise in TRAF3/BCL2 double-transgenic (tg) mice, all of which are characterized by the loss of surface IgM and IgD expression. However, two types of lymphomas are predominant: (1) mature B cell neoplasms consistent with diffuse large B cell lymphoma and (2) plasma cell neoplasms. The Ig isotypes expressed by the expanded B-cell clones included IgA, IgG and IgM, with most having undergone somatic hypermutation. In contrast, mouse littermates representing all the other genotypes (TRAF3-/BCL2-; TRAF3+/BCL2- and TRAF3-/BCL2+) did not develop significant lymphadenopathy or clonal B cell expansions within the observation period of 20 months. Interestingly, a large representation of the HCDR3 sequences expressed in the TRAF3-tg and TRAF3/BCL2-double-tg B cells are highly similar to those recognizing pathogen-associated molecular patterns and damage-associated molecular patterns, strongly suggesting a role for TRAF3 in promoting B cell differentiation in response to these antigens. Finally, allotransplantation of either splenocytes or cell-containing ascites from lymphoma-bearing TRAF3/BCL2 mice into SCID/NOD immunodeficient mice showed efficient transfer of the parental expanded B-cell clones. Altogether, these results indicate that TRAF3, perhaps by promoting exacerbated B cell responses to certain antigens, and BCL2, presumably by supporting survival of these clones, cooperate to induce mature B cell neoplasms in transgenic mice.